2015
DOI: 10.1016/j.neuron.2015.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Ablation, Silencing, and Activation Establish Glycinergic Dorsal Horn Neurons as Key Components of a Spinal Gate for Pain and Itch

Abstract: SummaryThe gate control theory of pain proposes that inhibitory neurons of the spinal dorsal horn exert critical control over the relay of nociceptive signals to higher brain areas. Here we investigated how the glycinergic subpopulation of these neurons contributes to modality-specific pain and itch processing. We generated a GlyT2::Cre transgenic mouse line suitable for virus-mediated retrograde tracing studies and for spatially precise ablation, silencing, and activation of glycinergic neurons. We found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
340
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(351 citation statements)
references
References 69 publications
11
340
0
Order By: Relevance
“…Notably, overall motor function (as assayed by rotarod, grip strength and ladder rung behaviors) remains mostly intact in all of these manipulations of the dI4/dIL A lineage (Duan et al, 2014;Fink et al, 2014;Foster et al, 2015;Kardon et al, 2014). This suggests that dI4/dIL A lineage inhibitory neurons are not necessary for gross motor function and, therefore, that inhibitory neurons in the ventral spinal cord are primarily responsible for gross motor behavior (Arber, 2012;Goulding et al, 2014).…”
Section: Inhibitory Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, overall motor function (as assayed by rotarod, grip strength and ladder rung behaviors) remains mostly intact in all of these manipulations of the dI4/dIL A lineage (Duan et al, 2014;Fink et al, 2014;Foster et al, 2015;Kardon et al, 2014). This suggests that dI4/dIL A lineage inhibitory neurons are not necessary for gross motor function and, therefore, that inhibitory neurons in the ventral spinal cord are primarily responsible for gross motor behavior (Arber, 2012;Goulding et al, 2014).…”
Section: Inhibitory Neuronsmentioning
confidence: 99%
“…These Ptf1a lineage neurons are a mixture of GABAergic and glycinergic neurons. Ablation of a subset of GABAergic neurons leads to defects in goal-directed reaching behavior and increased scratching behavior (Fink et al, 2014), while ablation or inhibition of glycinergic neurons (many of which also release GABA) leads to increased sensitivity to mechanical pain, thermal sensation and itch (Foster et al, 2015). While these studies have provided important insights, it should be noted that the manipulations could affect a large number of inhibitory neurons that comprise numerous subpopulations.…”
Section: Inhibitory Neuronsmentioning
confidence: 99%
“…Foster et al (42) also found evidence consistent with the strong innervation of spinal glycinergic interneurons by nonnociceptive sensory neurons. In addition, ablation of glycinergic neurons resulted in hypersensitivity and spontaneous aversive behaviors, whereas their exogenous activation ameliorated neuropathic hyperalgesia (41).…”
Section: Specific Glycine Alterationsmentioning
confidence: 80%
“…Interneurons represent the majority of the neural population throughout the dorsal horn, and are particularly dense in laminae I, II and III (Todd and Koerber, 2013). Certain interneurons are inhibitory; they attenuate the transmission of nociceptive messages through the release of GABA or glycine (Foster et al, 2015;Todd and Koerber, 2013).…”
Section: Mechanisms For Modulating Painmentioning
confidence: 99%